A prebreeding study of introgression spring bread wheat lines carrying combinations of stem rust resistance genes, Sr22+Sr25 and Sr35+Sr25 - S. N. Sibikeev; O. A. Baranova; A. E. Druzhin (Вавиловский журнал генетики и селекции)
The Sr22, Sr35, and Sr25 genes attract the attention of bread wheat breeders with their effectiveness against Puccinia graminis f. sp. tritici race Ug99 and its biotypes. The effectiveness and impact of Sr22+Sr25 and Sr35+Sr25 gene combinations on agronomic traits have not yet been studied. In the present article, these traits were studied using the spring bread wheat lines L503/W3534//L503, L503/Sr35//L503/3/L503 carrying the Sr22+Sr25 and Sr35+Sr25 genes during 2016–2020. These lines were assessed for resistance to P. graminis f. sp. tritici under natural epiphytotics and to the Saratov, Lysogorsk and Omsk populations of the pathogen and to the PgtZ1 (TKSTF) and PgtF18.6 fungus isolates in laboratory conditions (TKSTF + Sr33). The presence of the studied Sr-genes was confirmed by using molecular markers. Prebreeding studies were conducted during 2018–2020 vegetation periods. Under the natural epiphytotics of the pathogen and in the laboratory conditions, the Sr22+Sr25 combination was highly effective, while Sr35+Sr25 was ineffective. For grain yield, the lines with the Sr22+Sr25 and Sr35+Sr25 genes were superior to the recipient cultivar L503 in one year (Sr22+Sr25 in 2019; Sr35+Sr25 in 2018), with a decrease in 2020, but in general there were no differences. For the period 2018–2020, both combinations showed a decrease in 1000 grains weight and an increase in the germination-earing period. The line with Sr22+Sr25 genes showed insignificant effects on gluten and dough tenacity, but the ratio of dough tenacity to extensibility was higher, and flour strength, porosity and bread volume were lower; in the line with Sr35+Sr25 genes, the gluten content was lower, but the strength, tenacity of the dough and the ratio of dough tenacity to extensibility were higher, flour strength and the porosity of the bread were at the recipient level, but the volume of bread was lower.